EVALUASI KEBIJAKAN PENANGGULANGAN KEMISKINAN (Studi Pelaksanaan Perda Nomor 2 Tahun 2007 Tentang Penanggulangan Kemiskinan di Kabupaten Kutai Kartanegara) - Efri novianto (MAHAKAM: Jurnal Ilmu-Ilmu Sosial, 2012)
One of our national  goals is to realize people well-being. When local autonomy was applied, it is the mutual responsibility between local government and central government for making people prosperous. The government of Kutai Kartanegara District, in its effort to eradicate poverty, has issued Local Regulation Number 2 Year 2007. Based on the data analysis, it can be concluded that the implementation of Local Regulation Number 2 Year  2007 did not run well. This can be seen from the fact that some of the policies and programs did not work well. This was caused by the quality of Local Regulation Number 2 Year 2007 which was not good enough because it only regulated technical and operational matters. TKPKD as a coordinating forum for poverty eradication did not play its role and function optimally; there was still sectoral ego from each SKPD in implementing the poverty eradication program; data and information used as the basis for poverty eradication were old data that make  their reliability unguaranteed and the budget allocated for poverty eradication was very low and it was not comparable with the number of poor people in Kutai Kartanegara District. The outcomes of this Local Regulation showed that there was a decrease in the number of poor people in Kutai Kartanegara District either in macro level (survey) or micro level (census), while seen from its effectiveness, this Regulation was not effective in eradicating poverty in Kutai Kartanegara District. Keywords: Local Autonomy, Local Regulation, Poverty Eradication